Third generation of the family - Mumbai Archive Project Team (Jio Institute, 2024)
Pritman Nakhva, the third generation of the family to grow up in this house, worked as a chef abroad. He returned home during the COVID-19 pandemic and now assists his brother in the shipbuilding business. Their combined income runs the household.